Abuse of Authority in Procurement Under the Corruption Law - Asis; Devi Mutiara Sanni (Universitas Negeri Semarang, 2026)
Nowadays, the practice of corruption in government procurement of goods and services is becoming increasingly sophisticated, and it is not uncommon for perpetrators to hide behind formal procedures such as the determination of the Self-Estimated Price (Harga Perkiraan Sendiri/HPS). This becomes legally justifiable because Article 26, Paragraph (6) of Presidential Regulation No. 16 of 2018 states that the HPS is not the basis for calculating the amount of state financial loss. However, the crime of corruption in the context of procurement does not lie in the numerical difference, but rather in the malicious intent (mens rea) when abusing authority in the process of determining the HPS. This study uses a normative legal research method with a statutory and case approach. This research addresses the following issues: 1). Can the inflation of the Self-Estimated Price (HPS) fulfill the element of